Sigmoid colon carcinoma with focal neuroendocrine differentiation associated with ulcerative colitis: A case report. (2016) - Rifu, Kazuma; Koinuma, Koji; Horie, Hisanaga; Morimoto, Mitsuaki; Kono, Yoshihiko; Tahara, Makiko; Sakuma, Yasunaru; Hosoya, Yoshinori; Kitayama, Joji; Lefor, Alan Kawarai; Sata, Naohiro; Suzuki, Tsukasa; et al.
Highlights: Colorectal carcinomas with neuroendocrine differentiation in UC are rare entity. Most of clinical presentations are shared with adenocarcinomas associated with UC. However, malignant potential may be higher. Surgical treatment should be recommended, if tumors are resectable. Best chemotherapy for this tumor is unknown, and further studies are required. Abstract: Introduction: Neuroendocrine tumors of the colon and rectum are relatively rare compared to sporadic colorectal carcinoma. There are few reports of neuroendocrine tumors of the colon and rectum in patients with ulcerative colitis. Presentation of case: A patient with sigmoid colon carcinoma with focal neuroendocrine features is presented. A 32-year-old man, who had been followed for ulcerative colitis for 14 years, was found to have carcinoma of the sigmoid colon on routine annual colonoscopy, and he underwent laparoscopic total colectomy. Pathologic examination showed sigmoid colon adenocarcinoma with focal neuroendocrine features. Discussion: Most colorectal carcinomas associated with inflammatory bowel disease are histologically similar to the sporadic type, and tumors with neuroendocrine features are very unusual. Conclusion: Very rare case of sigmoid colon carcinoma with neuroendocrine features arising in a patient with UC was described.